2021
DOI: 10.3389/fphar.2021.618846
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Study of the Anti-Liver Injury Mechanism of Citri Reticulatae Pericarpium

Abstract: Liver diseases are mostly triggered by oxidative stress and inflammation, leading to extracellular matrix overproduction and prone to develop into liver fibrosis, cirrhosis and hepatocellular carcinoma. Liver injury (LI) refers to various pathogenic factors leading to the destruction of stem cells that then affect the liver’s normal function, causing a series of symptoms and abnormal liver function indicators. Citri Reticulatae Pericarpium (CRP) is one of the most commonly used traditional Chinese medicines; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…Radix Glycyrrhizae Polysaccharide , one of the chief bioactive components in Radix Glycyrrhizae , has been reported to participate in regulation of immunity and phagocytosis, as well as anticomplement [ 25 ]. Volatile oils and flavonoids in Pericarpium Citri Reticulatae are considered to be major components, which act alone or jointly to combat inflammatory responses and lipid peroxidation, followed by attenuating immunological reaction [ 26 ]. To conclude, the therapeutic effects resulting from combinations of couplet medicines are quite different.…”
Section: Discussionmentioning
confidence: 99%
“…Radix Glycyrrhizae Polysaccharide , one of the chief bioactive components in Radix Glycyrrhizae , has been reported to participate in regulation of immunity and phagocytosis, as well as anticomplement [ 25 ]. Volatile oils and flavonoids in Pericarpium Citri Reticulatae are considered to be major components, which act alone or jointly to combat inflammatory responses and lipid peroxidation, followed by attenuating immunological reaction [ 26 ]. To conclude, the therapeutic effects resulting from combinations of couplet medicines are quite different.…”
Section: Discussionmentioning
confidence: 99%
“…The higher node degree indicates that this gene may be more important, and the details of the specific gene name and its corresponding node degree are given in Supplementary Table S4 . In addition, we calculated the mean value of 106 overlapping gene degrees to be 15.05, selected all genes with value greater than the mean value [ 34 ], and generated 48 core targets of relatively more important networks with other gene interactions ( Figure 3(b) ). Moreover, to better highlight the importance of key targets, after processing these related targets using Cytoscape software, it displayed 48 genes with higher values in the inner loop of Figure 3(c) .…”
Section: Resultsmentioning
confidence: 99%
“…CRP, a traditional Chinese herbal medicine used in the clinic for centuries, has anti-in ammatory, antioxidant, anticancer and other bene cial properties according to modern pharmacological studies [22,24,34]. In addition, CRP may be effective for diseases affecting multiple systems, such as the digestive system, the respiratory system and particularly the cardiovascular system [22,27,35]. Accumulating evidence suggests that CRP has cardioprotective effects [15,16,36].…”
Section: Discussionmentioning
confidence: 99%
“…CRP has attracted increasing attention from researchers because it has multiple pharmacologic effects and rich resources with low toxicity and costs [23]. Modern pharmacological investigations have revealed that CRP can ght against in ammation, oxidative stress, atherosclerosis, thrombus, liver injury and tumors [22,[24][25][26][27]. Our prior studies showed that CRP can alleviate cardiac hypertrophy and brosis induced by Ang II and ISO via activating PPARγ [15,16].…”
Section: Introductionmentioning
confidence: 99%